2019
DOI: 10.3390/horticulturae5040078
|View full text |Cite
|
Sign up to set email alerts
|

A Susceptible Scion Reduces Rootstock Tolerance to Ralstonia solanacearum in Grafted Eggplant

Abstract: The bacterial wilt pathogen (Ralstonia solanacearum) is a highly pathogenic soil-borne bacterium that invades the vascular system of a host plant leading to plant wilting and death. In agricultural systems, tolerant rootstocks are usually used to enhance disease resistance and tolerance in crop plants to soil-borne pathogens. Here, two distinct eggplant cultivars with different tolerances to R. solanacearum infection, the disease-tolerant cultivar 'S21 and the disease-susceptible cultivar 'Rf', were used to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…This implies that defence intensity to pathogens might be altered depending on the compatibility between grafted plants. Actually, although there are no available research findings on PPN resistance or tolerance as far as we know, one study using reciprocal grafting with eggplant scions and rootstocks found that the susceptible scions impaired rootstock tolerance to the soilborne pathogen Ralstonia solanacearum species complex (Huang et al, 2019). Baker, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…This implies that defence intensity to pathogens might be altered depending on the compatibility between grafted plants. Actually, although there are no available research findings on PPN resistance or tolerance as far as we know, one study using reciprocal grafting with eggplant scions and rootstocks found that the susceptible scions impaired rootstock tolerance to the soilborne pathogen Ralstonia solanacearum species complex (Huang et al, 2019). Baker, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…It remains possible that the genes encoding IAI, SPS, and SuSy in grafted watermelon lines were downregulated by pumpkin rootstock. The grafted plant always maintains the exchange of substances between scion and rootstock, for example, various types of plant RNA species move from cell to cell or systemically to potentially regulate grafted plant physiological processes (Lewsey et al 2016, Huang et al 2019. Pumpkins generally accumulate lower amounts of sugar in fruit than cultivated watermelon varieties.…”
Section: Discussionmentioning
confidence: 99%
“…This shows that the susceptibility of the plant to pathogens can vary, depending on the characteristics of the graft and rootstock used. For example, it was observed that a susceptible graft could affect the response to the soil borne pathogen Ralstonia solanacearum in an eggplant rootstock [76]. This would indicate that the expression of the NBS-LRR genes associated with the gene-forgene resistance [77][78][79][80] in grafted plants could be mediated by the rootstock.…”
Section: Changes In Plant Defense Responses Induced By the Rootstockmentioning
confidence: 99%